2008
DOI: 10.1063/1.2838351
|View full text |Cite
|
Sign up to set email alerts
|

Strain development in nanoporous metallic foils formed by dealloying

Abstract: Articles you may be interested inStructural features and high quasi-static strain rate sensitivity of Au49Cu26.9Ag5.5Pd2.3Si16.3 bulk metallic glass Appl. Phys. Lett. 101, 241905 (2012); 10.1063/1.4770072 Morphology and porosity of nanoporous Au thin films formed by dealloying of AuxSi1−x J. Appl. Phys. 112, 094320 (2012); 10.1063/1.4764906 Morphological and topological analysis of coarsened nanoporous gold by x-ray nanotomography Appl. Phys. Lett. 96, 043122 (2010); 10.1063/1.3285175 Fabrication of metallic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 22 publications
2
40
2
Order By: Relevance
“…In fact, when the ligaments of NPG are modelled as idealised long cylinders, then the action of surface stress is to compress the cylinder axially and expand it in the radial direction [86]. The Bragg reflection asymmetry in reference [34] is therefore naturally consistent with surface-induced strain in nanoscale structures -the same region tends to be strained differently in different orientations. Yet, our study failed to observe a significant peak asymmetry in either, the experimental or the virtual diffraction patterns.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, when the ligaments of NPG are modelled as idealised long cylinders, then the action of surface stress is to compress the cylinder axially and expand it in the radial direction [86]. The Bragg reflection asymmetry in reference [34] is therefore naturally consistent with surface-induced strain in nanoscale structures -the same region tends to be strained differently in different orientations. Yet, our study failed to observe a significant peak asymmetry in either, the experimental or the virtual diffraction patterns.…”
Section: Discussionmentioning
confidence: 95%
“…The origin of this discrepancy is unclear. One observation is that reference [34] reported the asymmetry only for samples investigated very shortly after dealloying; this might point towards a transient state of very freshly dealloyed NPG. Such states were not explored in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The surface morphology differed significantly according to the HF concentration. Similar to bicontinuous nanoporous structures dealloyed from crystalline alloy systems, [1][2][3][4][5][6] treating the sample with 0.05 M HF solution gave a nanoporous structure. A denser surface was obtained by treating with 0.1 M HF solution.…”
Section: Methodsmentioning
confidence: 99%
“…1,2) Although dealloying has received attention in the context of corrosion, it has recently been receiving renewed attention because particular systems exhibit nanostructure or nanoporosity evolution upon dealloying. 1,2) Interesting dealloying behaviors have been observed for binary systems, including Ag-Au, [1][2][3][4][5] Cu-Zr, [6][7][8] Cu-Pt, 9) and Pt-Si. 10) Compared to the crystalline alloys, multicomponent metallic glasses are monolithic in phase with a homogeneous composition and structure down to the subnanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…This process leads to the formation of a porous structure that has been imaged using both transmission X‐ray microscopy and electron microscopy . X‐ray diffraction (XRD) is generally used to monitor the crystalline strain and XRD studies have shown that dealloying induces strain, which could ultimately be used to tune the catalytic properties, among others, of dealloyed materials. While bulk strains during dealloying have been measured, they are averaged over significant mesoscale heterogeneity.…”
Section: Introductionmentioning
confidence: 99%